2018
DOI: 10.3390/su10103488
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Conservation Participation by Local Communities in Gaurishankar Conservation Area Project, Nepal

Abstract: Information about the factors associated with conservation participation by local communities is important to garner support and involvement within a natural protected area. This research examined how residents’ natural resource dependency and other social, economic, and access-related variables predict conservation participation. Data were collected based on a stratified random sampling of households from Gaurishankar Conservation Area Project (GCAP)—a newly designated mountainous protected area in Nepal. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…These Hill districts, including Kaski, Parbat, Syangja, and Tanahu, have higher development patterns [63] following Kathmandu valley and higher water productivity than other districts in the country [64]. Few clusters in the eastern Mountain region could be attributed to well-developed tourism infrastructure, which has high impacts on our CDRI variables [65,66]. Our study shows, in comparison to Aksha, Juran [52], that resilience and vulnerability are not opposing concepts to each other, but rather they do overlap to some extent [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…These Hill districts, including Kaski, Parbat, Syangja, and Tanahu, have higher development patterns [63] following Kathmandu valley and higher water productivity than other districts in the country [64]. Few clusters in the eastern Mountain region could be attributed to well-developed tourism infrastructure, which has high impacts on our CDRI variables [65,66]. Our study shows, in comparison to Aksha, Juran [52], that resilience and vulnerability are not opposing concepts to each other, but rather they do overlap to some extent [5,22].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, tourism development in PAs and NPs has been a robust tool in poverty reduction and local empowerment [38,39]. Relatedly, community involvement in the planning process is crucial to ensure the effectiveness of conservation initiatives, however, lack of local participation in the decision-making can lead to unsustainable consumption of natural resources and create conflict with management [25,30,40]. Furthermore, there is a growing issue associated with human-wildlife conflict, which can contribute to loss of habitat and result in fatalities in both animal and human populations [41,42].…”
Section: Protected Area Managementmentioning
confidence: 99%
“…Poor households are usually high in resource dependency and more vulnerable to the costs of restriction from the PA (Rahman et al, 2017). Attitudinal studies additionally reported that communities will not be motivated enough to support conservation unless the benefits from the PA offset their costs (Coad et al, 2008;Nepal and Spiteri, 2011;Paudyal et al, 2018). A good example is the Koshi Tappu Wetland in Nepal, where the incentive program to harvest grass and thatch as livelihood support could not successfully integrate local communities because its benefits were too little when compared with the economic loss of resource restriction (Shrestha and Alavalapati, 2006).…”
Section: Introductionmentioning
confidence: 99%